Modification of high volume fly ash composites containing calcined stöber nano-SiO2 particles. (1st July 2022) - Tian, Liang; Zhang, Fangzheng; Chen, Juncheng; Sun, Jinfeng; Zhu, Huajun
Abstract: The present study aims to explore the influence of 2 wt% calcined stöber nano-SiO2 (CSNS) on hydration properties of high volume fly ash (HVFA) system made with 50 wt% and 70 wt% of cement replacement up to 28 days. In the first part, the reactivity of lab-synthesized CSNS was evaluated based on a simulated pore solution method. The morphology and microstructure of the potential reaction products were analyzed. In the second part, the effect of SNS and CSNS on the preliminary cement hydration was compared by using isothermal calorimetry. Finally, the effects of CSNS on compressive strength, and water absorption were evaluated in HVFA mortars and the microstructural developments were studied in HVFA pastes by analyzing phase changes and pore structures. The experimental results show that both SNS and CSNS presented low pozzolanic activity within 3 days, but can be completely consumed up to 28 days, with the formation of lamelliform calcium silicate hydrate gel. CSNS effectively overcame the negative effects of SNS on cement hydration, and further accelerated cement hydration. This is possible because the hydroxyl group was removed after calcination of SNS, which made the well-dispersed CSNS better accelerate cement hydration by effective nucleation sites and filler effects. 2 wt% CSNS significantly contributed to generating more hydrates and refining pore structures in HVFA cement pastes, which increased the compressive strength of HVFA mortar up to 28 days and also significantly decreased its 28-day water absorption. Highlights: CSNS presented low pozzolanic activity within 3 days. CSNS can be completely consumed up to 28 days in a simulated pore solution. CSNS can effectively offset the negative effects of the stöber nano-SiO2 on cement hydration. 2 wt% CSNS dramatically enhanced the properties of HVFA-based cement pastes or mortars.